2009
DOI: 10.1002/ijc.24165
|View full text |Cite
|
Sign up to set email alerts
|

DNA adduct formation and induction of micronuclei and mutations in B6C3F1/Tk mice treated neonatally with acrylamide or glycidamide

Abstract: Acrylamide, a food contaminant, is carcinogenic in experimental animals, with both genotoxic and nongenotoxic pathways being proposed. To obtain information regarding mechanisms of acrylamide tumorigenesis, we compared the extent of DNA adduct formation and induction of micronuclei and mutations in mice treated neonatally with acrylamide and its electrophilic metabolite glycidamide. Male and female B6C3F 1 /Tk mice were treated intraperitoneally on postnatal days (PNDs) 1, 8 and 15 or PNDs 1-8 with 0.14 or 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 53 publications
(98 reference statements)
4
32
0
Order By: Relevance
“…The i.p. exposure to AA on PND1-8 also increased mutations at the TK and hprt loci in spleen lymphocytes of mice (von Tungeln et al, 2009) and at lac Z loci in transgenic mice (Muta®Mouse) (Hoorn et al, 1993).…”
Section: Genotoxicitymentioning
confidence: 93%
“…The i.p. exposure to AA on PND1-8 also increased mutations at the TK and hprt loci in spleen lymphocytes of mice (von Tungeln et al, 2009) and at lac Z loci in transgenic mice (Muta®Mouse) (Hoorn et al, 1993).…”
Section: Genotoxicitymentioning
confidence: 93%
“…In the assessment of mutagenic eŠects induced by AA and its metabolite GA, the cell subclones employed in TK and HPRT gene mutation assays include L5178Y TK +/-mouse lymphoma cell (18,(28)(29)(30), human lymphoblastoid cell TK6 (31), Chinese hamster ovary (CHO) cell (32), Chinese hamster V79 cell (33)(34)(35) and human promyelocytic leukaemia cells HL-60 and NB4 (36). More recently, the development of the mammalian cell gene assays employing rodent lymphocytes has also contributed signiˆcantly to the understanding of in vivo somatic cell mutagenesis induced by AA, including the assays performed in Big Blue mice, B6C3F1/TK mice and Big Blue rats (37)(38)(39).…”
Section: Mammalian Gene Mutation Assays At the Hprt And Tk Locimentioning
confidence: 99%
“…Mutagenicity of AA and GA at the HPRT Locus in DiŠerent Test Systems GA is consistently mutagenic at HPRT mutation assays in various test systems involving mammalian cell lines (32,34,35) and rodents (37)(38)(39). On the contrary, some studies suggested that AA may not induce gene mutation in HPRT test.…”
Section: Mammalian Gene Mutation Assays At the Hprt And Tk Locimentioning
confidence: 99%
See 2 more Smart Citations